Molecular characterization of a complex, recombinant human immunodeficiency virus type 1 (HIV-1) isolate (A/G/J/K/?): evidence to support the existence of a novel HIV-1 subtype. - Paraskevis, D; Magiorkinis, E; Magiorkinis, G; Anastassopoulou, C; Lazanas, M; Chrysos, G; Vandamme, A; Hatzakis, A (2001)
Recombination is one of several factors that contribute to the great genetic diversity of human immunodeficiency virus type 1 (HIV-1). In the current study, analysis of the full-length genome of a novel complex mosaic HIV-1 isolate (99GR303) from a Greek sailor who was possibly infected in Sierra Leone, Africa is presented. The 99GR303 isolate was found to comprise genomic regions belonging to subtypes A, G, J and K as well as of regions of a subtype that remains unclassified. For a partial region of env as well as vpr, no apparent similarity to the known HIV-1 subtypes or to any of the circulating recombinant forms was found. In fact, in the partial env gene, including the C2-V3 region, the 99GR303 isolate formed a new clade, suggesting the existence of an additional HIV-1 subtype. Thus, novel recombinants embody partial genomic regions which may have originated either from subtypes that existed in the past and became extinct or from contemporary subtypes that are extremely rare.